1999
DOI: 10.1002/etc.5620181131
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ecotoxicity of hydrocarbon‐contaminated soils using physicochemical parameters

Abstract: Abstract-The physicochemical properties of eight hydrocarbon-contaminated soils were used to predict toxicity to earthworms (Eisenia fetida) and plants. The toxicity of these preremediated soils was assessed using earthworm avoidance, survival, and reproduction and seed germination and root growth in four plant species. No-observed-effect and 25% inhibitory concentrations were determined from the earthworm and plant assays. Physical property measurements and metals analyses of the soils were conducted. Hydroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…In juvenile F. grandis crude oil, acute toxicity was not correlated to any of the individual petroleum chemicals, PAH classes, or target PAHs and expanded target PAHs measured as potential indicators of toxicity. Crude oil WAF toxicity is assumed to be more closely related to total petroleum hydrocarbons (TPHs), which include the heterocyclic aromatics, monocyclic aromatics, and alkyl benzenes [49]; but our observation that toxicity measurements and chemical measurements were only weakly related agreed with the observations of previous researchers who have found no or only weak relationships between TPHs, total PAHs, and/or individual hydrocarbons when such assumptions are tested [13,[50][51][52]. We hypothesize that chemical measurements and toxicity measurements are poorly related in the present study and in previous work [12,[50][51][52] because there are tens of thousands of compounds in crude oil [7,8], but GC-MS currently quantifies less than 150 of those compounds [25].…”
Section: Acute Mortality and Modelingsupporting
confidence: 84%
“…In juvenile F. grandis crude oil, acute toxicity was not correlated to any of the individual petroleum chemicals, PAH classes, or target PAHs and expanded target PAHs measured as potential indicators of toxicity. Crude oil WAF toxicity is assumed to be more closely related to total petroleum hydrocarbons (TPHs), which include the heterocyclic aromatics, monocyclic aromatics, and alkyl benzenes [49]; but our observation that toxicity measurements and chemical measurements were only weakly related agreed with the observations of previous researchers who have found no or only weak relationships between TPHs, total PAHs, and/or individual hydrocarbons when such assumptions are tested [13,[50][51][52]. We hypothesize that chemical measurements and toxicity measurements are poorly related in the present study and in previous work [12,[50][51][52] because there are tens of thousands of compounds in crude oil [7,8], but GC-MS currently quantifies less than 150 of those compounds [25].…”
Section: Acute Mortality and Modelingsupporting
confidence: 84%
“…Salanitro et al (1997) concluded that bioremediation of crude oil-spiked soil was effective in alleviating all toxicity to earthworms, despite high residual oil concentrations of 4500-10 000 mg kg 21 . However, Wong et al (1999) found that earthworm toxicity was correlated with hydrocarbon concentrations; TPH explained 65% of the variance in the earthworm toxicity data.…”
Section: Comparative Ecotoxicological Studiesmentioning
confidence: 94%
“…The effect values found here are lower than the ones reported by other authors [10,40], which could be due to differences in oil types or soils characteristics (e.g., organic matter contents). Based on work by Salanitro et al [8], Dorn et al [10], Saterbak et al [2], and Wong et al [1], Dorn and Salanitro [9] concluded that oil levels Ͻ4,000 mg/kg dry soil will have little effect on plants and earthworms. Their studies, however, mainly focused on acute effects and used shorter exposure periods than applied here.…”
Section: Toxicity Of Oilmentioning
confidence: 99%
“…Chemical analysis usually is insufficient to provide insight into the potential ecological risk of polluted soils since it does not allow for an integration of the combined effects of the mixture of all chemicals present at a polluted site, including their bioavailability [1,2]. Bioassays do integrate these effects and are therefore recommended for the ecological risk assessment of polluted soils [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation